What young people report about the personal characteristics needed for social science research after carrying out their own investigations in an after-school club. Issue 3 (27th May 2018) - Kerawalla, Lucinda; Messer, David J.
Abstract: Several arguments have been put forward about the benefits of young people carrying out their own social science research in terms of empowering their voices and their participation. Much less attention has been paid to investigating the understandings young people develop about the research process itself. Seven twelve-year olds carried out self-directed social science research into a topic of their choice. Towards the end of their six months experience, we used a questionnaire and follow-up semi-structured interviews to investigate, from a sociocultural perspective, what the young people thought about being a researcher. Thematic analysis of the interviews identified three themes and eight subthemes suggesting that they were aware of: the need to demonstrate researcher/research integrity (be thorough, truthful, orderly, and have a good understanding of research process); the need for good interpersonal skills and standards, and good self-management skills (be resilient, agentic, committed and good at time management). We discuss how first-hand social science research experience might: be relevant to several areas of schooling; give young people experience of the personal characteristics important for success; help young people to realise that they can be social science researchers, and offer advanced and novel learning experiences outside the constraints of the school curriculum.